RANCANG BANGUN APLIKASI SIRKULASI ARSIP PADA DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR - Dzulmi, Abu Rizal; Suhandiah, Sri; Ayuningtyas, Ayuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2020)
The Library and Archives Office (Disperpusip) of East Java Province is one of the implementers of regional policies.Â It focuses on the sector of the library and archives. There are some problems faced by Disperpusip. The archive search method which can only be done by looking at the inventory list. The availability of the archives and the staffs are not at their place, this leads the users to wait. Another problem is, the reporting method is done manually, which prone to lost or damaged. To solve the problems, an archive circulation application for Disperpusip needs to develop.Â The app can handle a few processes such as archive search, orders, borrow and return, and also report making. It is web-based so it can run on all operating systems and lots of media such as computers desktop and phones.